The Relationship Between Nutritional Status and Quality of Life in Older Adults at Nursing Homes Jambangan, Surabaya - Sahlatun Nuha Tsana; Amalia Ruhana; Endang Sri Wahyuni; Satwika Arya Pratama (MBUnivPress, 2024)
Nursing homes were built by the government of Indonesia in response to the country's growing senior population. Given their helplessness, nursing facilities can be safe places for the elderly to dwell. Aging is a natural phenomenon that affects all elderly people. It causes many changes in the elderly that may have an impact on their quality of life and nutritional status. The purpose of this study is to describe the elderly at UPTD Griya Wreda Jambangan Surabaya's nutritional state, quality of life, and the relationship between the two. This study uses a quantitative research design. Using the purposive sample approach, a total of sixty samples from the senior population were chosen. The World Health Organization Quality of Life - BREF (WHOQoL - BREF) and Mini Nutritional Assessment (MNA) are the measures that are utilized, and both have demonstrated validity and reliability. The study's findings indicated that 33 elderly (55%) were at risk of malnutrition, 24 elderly (40%) had good nutrition, and 3 elderly (5%) were exposed to malnutrition. In addition, the study's findings indicated that 45 elderly (75%) had good quality of life, and 15 elderly (25%) had poor quality of life. Based on the highest score, the elderly have the most satisfied perceptions in the quality of life domain based on physical health 42 elderly (70%) and psychological health 34 elderly (57%).In this study, the relationship between quality of life and nutritional status was analyzed using the Pearson test. In this study, the relationship between quality of life and nutritional status was analyzed using the Pearson correlation test. The results of the analysis showed a significant relationship between nutritional status and quality of life (P=0.0036). Based on these results, it can be concluded the connection between nutritional status and quality of life in the elderly at the Jambangan Nursing Home in Surabaya.